Inhibition of 5-Lipoxygenase Selectively Triggers Disruption of c-Myc Signaling in Prostate Cancer Cells - Sarveswaran, Sivalokanathan; Chakraborty, Debrup; Chitale, Dhananjay; Sears, Rosalie; Ghosh, Jagadananda (The Journal of biological chemistry, 2015)
Myc is up-regulated in almost all cancer types and is the subject of intense investigation because of its pleiotropic effects controlling a broad spectrum of cell functions. However, despite its recognition as a stand-alone molecular target, development of suitable strategies to block its function is hindered because of its nonenzymatic nature. We reported earlier that arachidonate 5-lipoxygenase (5-Lox) plays an important role in the survival and growth of prostate cancer cells, although details of the underlying mechanisms have yet to be characterized. By whole genome gene expression array, we observed that inhibition of 5-Lox severely down-regulates the expression of c-Myc oncogene in prostate cancer cells. Moreover, inhibition of 5-Lox dramatically decreases the protein level, nuclear accumulation, DNA binding, and transcriptional activities of c-Myc. Both the 5-Lox inhibition-induced down-regulation of c-Myc and induction of apoptosis are mitigated when the cells are treated with 5-oxoeicosatetraenoic acid, a metabolite of 5-Lox, confirming a role of 5-Lox in these processes. c-Myc is a transforming oncogene widely expressed in prostate cancer cells and maintains their transformed phenotype. Interestingly, MK591, a specific 5-Lox inhibitor, strongly affects the viability of Myc-overactivated prostate cancer cells and completely blocks their invasive and soft agar colony-forming abilities, but it spares nontransformed cells where expression of 5-Lox is undetectable. These findings indicate that the oncogenic function of c-Myc in prostate cancer cells is regulated by 5-Lox activity, revealing a novel mechanism of 5-Lox action and suggesting that the oncogenic function of c-Myc can be suppressed by suitable inhibitors of 5-Lox. Background: Frequent overactivation of c-Myc aggravates a spectrum of cancers. However, cancer-specific inhibition of c-Myc activity poses significant difficulty. Results: Inhibition of 5-lipoxygenase down-regulates c-Myc expression and triggers proteasomal degradation in cancer cells but not in normal fibroblasts. Conclusion: Inhibition of 5-lipoxygenase selectively disrupts c-Myc function in cancer cells. Significance: Inhibition of 5-lipoxygenase may be a novel strategy to control oncogenic c-Myc signaling.